The value of a tram station on local house prices: an hedonic modelling approach. (2nd September 2019) - Higgins, David M; Rezaei, Alireza; Wood, Peter
ABSTRACT: There are many drivers of house prices. In urban locations, public infrastructure is considered one of the leading determinants. To explore this relationship, an Hedonic house pricing model was applied to an established Birmingham, the UK working class residential area which is serviced by the Metro Midland tram line. The selected Wednesbury Great Western Street station provides ease of access for the local residents to Birmingham and Wolverhampton City Centres plus there has been recent sale evidence of 100 properties within close proximity to the station. Independent variables consisted of a range of typical physical, locational and neighbourhood attributes for the Hedonic house pricing model input data. Based on the preferred linear Hedonic model, the findings from the recent 100 Wednesbury house sales showed property type, bedrooms, floor area, ambience and distance to the tram station were key explanatory factors in relation to pricing levels. On the evidence provided, property price increased by £16, 878 for every km closer to the tram stop. However, when examining properties within defined distance bands with smaller datasets, the location to the tram station was not a significant statistical driver. This suggests that proximity to a public transport access point alongside key housing characteristics should form part of the housing decision making process as they are significant predictors of local house prices.